Self-Financing Roads - Erik T. Verhoef; Herbert Mohring (Tinbergen Institute, 2007)
Mohring and Harwitz (1962) showed that, under certain conditions, an optimally designed and priced road would generate user toll revenues just sufficient to cover its capital costs. Several scholars subsequently explored the robustness of that finding. This paper briefly summarizes further research on the relationship between congestion-toll revenues and road costs. Despite its transparency, the self-financing theorem can lead to erroneous interpretations. The paper's second part discusses three such possible fallacies. It uses a simple numerical model to investigate them. The model shows that the naïve interpretation of the Mohring-Harwitz rule may lead to substantial welfare losses. These losses are particularly prominent when the difference between capital and investment cost is confused and when balanced-budget constraints are imposed under second-best network conditions. In contrast, losses from imposing a balanced-budget constraint when economies or diseconomies of scale exist are surprisingly small.
Keywords: R41; R48; D62; 330; Traffic congestion; Road pricing; Road capacity choice; Road financing; Verkehrsstau; Straßenbenutzungsgebühr; Verkehrsplanung; Straßenbaufinanzierung; Verkehrsökonomik; Theorie